2016
DOI: 10.1111/joms.12195
|View full text |Cite
|
Sign up to set email alerts
|

Business Statesman or Shareholder Advocate? CEO Responsible Leadership Styles and the Micro‐Foundations of Political CSR

Abstract: International audienceIn this article we pursue two objectives. First, we refine the concept of responsible leadership from an upper echelon perspective by exploring two distinct styles (instrumental and integrative) and thereby further develop the understanding of the newly emerging integrative style. Second, we propose a framework that examines the micro-foundations of political corporate social responsibility (CSR). We explicate how the political CSR engagement of organizations (in social innovation and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
289
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 233 publications
(309 citation statements)
references
References 133 publications
(231 reference statements)
11
289
0
9
Order By: Relevance
“…Miska and Mendenhall (2015) suggest that neuroscience research could investigate the cognitive and emotional challenges of responsible leaders who try to address a diversity of stakeholder demands and could foster our understanding of the neural mechanisms related to corporate social responsibility and sustainability. Maak et al (2016) argue that cognitive and social complexity and a social-welfare orientation are conducive for a form of responsible leadership that is able to integrate diverse stakeholder concerns and competing goals. It would be interesting to research the neural correlates of such cognitive complexity and social value orientations.…”
Section: Leadershipmentioning
confidence: 99%
“…Miska and Mendenhall (2015) suggest that neuroscience research could investigate the cognitive and emotional challenges of responsible leaders who try to address a diversity of stakeholder demands and could foster our understanding of the neural mechanisms related to corporate social responsibility and sustainability. Maak et al (2016) argue that cognitive and social complexity and a social-welfare orientation are conducive for a form of responsible leadership that is able to integrate diverse stakeholder concerns and competing goals. It would be interesting to research the neural correlates of such cognitive complexity and social value orientations.…”
Section: Leadershipmentioning
confidence: 99%
“…including CEO narcissism (Tang, Mack, & Chen, 2018), CEO confidence (McCarthy, Oliver, & Song, 2017), CEO power (Muttakin, Khan, & Mihret, 2018), CEO tenure (Chen, Zhou, & Zhu, 2018), CEO traits (Myung, Choi, & Kim, 2017) as well as CEO responsible leadership style (Maak, Pless, & Voegtlin, 2016). Though the effect of CEOs' characteristics on CSR has been widely analyzed, the premise that this effect is stable across various contexts is problematic, which makes the contextualization quite necessary.…”
mentioning
confidence: 99%
“…Therefore, fostering CEO responsible leadership seems decisive (Maak et al, 2014). As many CEOs have a strong sense of fiduciary duty toward the owners of their company, one policy implication for publicly listed companies would be to encourage responsible investing that puts an emphasis on CSR topics.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive complexity enables leaders to recognize and comprehend various interests and to deal with a greater multitude of news and information; relational complexity comprises the ability to communicate and negotiate with different groups and is based on emotional intelligence and cultural sensitivity; behavioral complexity is the capacity to draw on a broad behavioral repertoire, including different leadership roles and to display these different roles in interactions with diverse stakeholders and to switch between (sometimes conflicting) roles, depending on the setting or situation (Maak et al, 2014;Hooijberg et al, 1997;Hannah et al, 2013). Denison et al (1995) showed that leaders who possess a higher capacity for behavioural complexity and can perform multiple and contradictory roles simultaneously are more effective; yet, they might also be able to act more responsible.…”
Section: Discussionmentioning
confidence: 99%